Sociology of Public Elementary Schools: Teachers' Role as Agents of Socialization for Religious Moderation Values in the Classroom - Anggraeni, Adiska Nur; Hanif, Muh. (ARZUSIN, 2026)
Although religious moderation has become an important agenda in character education, limited research has examined how public elementary school teachers function sociologically as agents of value socialization in rural school contexts. This study aims to examine the role of public elementary school teachers as agents of socialization for religious moderation values in classroom learning. Employing a qualitative approach with a single case study design, the study was conducted at SDN Rejasari, Banjarmangu District, Banjarnegara Regency, Central Java, during the 2025–2026 academic period. Data were collected through in-depth interviews, participant observation, and curriculum document analysis, focusing on the strategies and practices implemented by Islamic Education (Pendidikan Agama Islam/PAI) teachers and classroom teachers. The findings reveal three key dimensions. First, PAI teachers simultaneously perform four roles in instilling religious moderation values: conservator, innovator, transmitter, and transformer. Second, the values socialized include justice (‘adl), balance (tawazun), moderation (i‘tidal), and unity and brotherhood (ukhuwah), which are internalized through exemplary behavior, classroom discussion, interfaith activities, and cross-subject integration. Third, the effectiveness of value socialization is strongly supported by teacher–parent collaboration and a conducive school environment, while the main obstacle is the limited direct interaction among students from different religious backgrounds. This study contributes to the development of religious moderation socialization models in rural public elementary school contexts and offers practical implications for strengthening character education curricula.